Factors associated with non-adherence to antihypertensive treatment in patients with social security - Pocohuanca-Ancco, Lucy (2021)
Background: Lack of adherence to antihypertensive therapy contributes directly to patients coexisting with hypertension, triggering increased risk of morbidity and mortality. Thus, nonadherence to treatment becomes one of the main causes of uncontrolled hypertension in the population. We evaluated the factors associated with non-adherence to antihypertensive treatment in cardiology patients of an EsSalud hospital in San Juan de Lurigancho-Lima, during 2017. Material and Methods: Analytical-crossover study, patients attending cardiology outpatient clinic with previous history of essential hypertension were included and secondary hypertension due to other biological causes were excluded. The Morisky-Green Morisky Medication Adherence Scale (MMAS-4) was used to assess non-adherence to antihypertensive treatment. Results: Of the 270 study participants, 69% (n=185) were adults older than 65 years, 46% (n=124) were male and 76% (n=118) had a stable partner. Among the clinical history, 60% (n=122) reported clinical diagnosis of arterial hypertension, 30% (n=80) of type II diabetes mellitus and 27% (n=73) non-adherence to treatment. Factors associated with non-adherence to treatment were male sex (ORa: 0.45, 95%CI 0.20-1.04), self-employed (ORa:3.88, 95%CI 1.51-9.97), BMI greater than 30 (ORa:0.23, 95%CI 0.07-0.70). Conclusions: in patients with a diagnosis of essential hypertension there are modifiable and non-modifiable risk factors associated with non-adherence to treatment. These factors should be considered in order to implement screening strategies and target interventions to adhere to treatment in reluctant patients.